Improving Health Independence with a Family-Based Complementary Therapy Approach: Peningkatan Kemandirian Kesehatan dengan Pendekatan Terapi Komplementer Berbasis Keluarga - Widaryanti, Rahayu; Muflih, Muflih; Dian Rhesa Rahmayanti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Purwomartani has local wisdom regarding the use of complementary therapies, but skills in using complementary therapies are obtained from generation to generation and are still not based on evidence-based so it can be at risk of injury. The purpose of this activity is to increase the ability and skills to use complementary therapy at the family level. This community service activity was carried out in June-July 2023 and was attended by 32 participants. The method used is health screening, health education, and utilization of herbs. The results of the health screening were 3 toddlers who had irregularities, 15 people who had blood pressure above normal, 10 people who had blood sugar levels above normal, and 8 people who had uric acid levels above normal. There is an increase in knowledge about the use of complementary therapy at the family level before and after the activity as much as 20.45 points.